Rational Choices of Farmers in Sustaining Agriculture Amid Tourism Expansion in Batu City - Sofiurrohman Sofiurrohman; Anif Fatma Chawa; Iwan Nurhadi; Moch Hisyam Putra (Jurnal Mamangan, 2025)
The rapid conversion of agricultural land into tourism areas in Batu City has driven many farmers to shift into the tourism sector. However, some farmers rationally choose to remain in agriculture despite increasing pressures and attractions of tourism. This study examines the rationality behind farmers’ decisions to sustain farming and the strategies they adopt amid agrarian crisis and tourism expansion. Guided by James S. Coleman’s rational choice theory, the analysis emphasizes actors’ calculations of resources, risks, and values. A qualitative case study was conducted in Bulukerto Village, Bumiaji District, Batu City, using semi-structured interviews, non-participant observation, and document analysis. The findings show that farmers’ persistence is shaped by the availability of land and agricultural resources, strong socio-cultural attachments, and careful assessments of tourism’s uncertainties, which are often unstable and capital-intensive. Rather than abandoning farming, they adapt by diversifying to more resilient or profitable commodities, including oranges, vegetables, cut flowers, and multi-purpose tree species. The study concludes that sustaining agriculture constitutes a rational choice grounded in economic stability, ecological sustainability, and cultural identity. The novelty of this research lies in showing how farmers’ rationality is formed not only by material resources but also by non-material values and perceived risks of tourism, offering new insights into agrarian transformation.